Evaluation of Physical Activities Recommendation Methodology for Blood Glucose Level Regulation - Igor Kulev; Saso Koceski; Elena Vlahu-Gjorgievska; Vladimir Trajkovi (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
Providing patients with convenient health facilities at a low cost has always been a great challenge for health service providers. Moreover, the fast changing life style of the modern world and the problem of aging society pose an urgent need to modernize such facilities. The emphasis has to be paid on  providing  health  monitoring in out-of-hospital conditions for elderly people and patients who require regular supervision, particularly in remote areas. This paper presents a recommendation algorithm, which incorporates collaboration and classification techniques in order to generate recommendations and suggestions for the physical activities that the users should carry out in order to improve their health. The algorithm has been evaluated using generic data and considering the daily food intake. The results of the experimental evaluation show that the algorithm is robust and could suggest the physical activities that might compensate the influence of the food intake over the blood glucose level.